Longwood Shola Watchdog Committee - an Experiment in Shola Management in Tamil Nadu - Sekar, T. (Indian Forester, 2002)
Sholas which represent a form of montane wet temperate forests occur predominantly in sheltered pockets of the Nilgiris and Upper Palnis of Tamil Nadu. They are also recorded in higher altitudes of Western Ghats in other districts of the State. As Sholas constitute a unique ecosystem with vast richness in biodiversity and provide many social benefits like sustenance of water supply in the hills , their protection has assumed greater significance in the last few decades. Sholas underwent considerable loss due to land use changes , fire and pressure from biotic factors. Protection of Shola forests against biotic pressure by way of fencing pockets of Sholas , artificial regeneration of Shola tree species in degraded portions and eco-restoration of old Blue gum (Eucalyptus globulus) areas with Sholas , fire protection are a few strategies being followed by the Tamil Nadu Forest Department to conserve and enhance the condition of the shola ecosystem. To involve the local communities in Shola preservation , a few of the interested citizens of Kotagiri Taluk in Nilgiris District have been formed into a committee called 'Longwood Shola Watchdog Committee'. The approaches adopted and activities that are being undertaken by this committee and result of such initiatives in protecting Longwood R.F. in Nilgiris North Forest Division Coimbatore Circle are discussed in this paper.